Aplikasi Location Based Service (LBS) Cafe Berbasis Android Di Kota Bandar Lampung - Reka Ramadhan; Arie Setya Putra; Khozainuz Zuhri (Jurnal Teknologi dan Informatika (JEDA), 2022)
The cafe has become a popular place to be used as a gathering place with family and friends, because it is an uncomfortable and cool place to be used as a gathering place and a means to socialize, and on the other hand there is still a lack of information media that can be used to find information from an existing cafe. in a city, the android application created in this study can be used as a medium of information in searching for data, coordinates, and distance from a cafe. The goal is to make it easier for local residents and tourists who want to find references for gathering places such as cafes. The author got a solution with the creation of an Android-based mobile application with the title of the report entitled Application Location Based Service (LBS) Bandar Lampung City Cafe Based on Android. The results of the Android-Based Location Based Service Cafe application in Bandar Lampung City can work well while making it easier for the people of Bandar Lampung City and outside the city to obtain information from the café contained in the application.